The Cambridge companion to Thucydides - Low, Polly (Cambridge University Press, 2023)
"Thucydides' History of the Peloponnesian War is one of the earliest and most influential works in the western historiographical tradition. It provides an unfinished account of the war between Athens and her allies and Sparta and her allies which lasted from 431 to 404 BC, and is a masterpiece of narrative art and of political analysis. The twenty chapters in this Companion offer a wide range of perspectives on different aspects of the text, its interpretation and its significance. The nature of the text is explored in detail, and problems of Thucydides' historical and literary methodology are examined. Other chapters analyse the ways in which Thucydides' work illuminates, or complicates, our understanding of key historical questions for this period, above all those relating to the nature and conduct of war, politics, and empire. Finally, the book also explores the continuing legacy of Thucydides, from antiquity to the present day"--
Includes bibliographical references and index
Keywords: Thucydides; Thucydides -- Themes, motives; Thucydides -- Influence; Greece -- History -- Peloponnesian War, 431-404 B.C -- Historiography; Aufsatzsammlung